2009
DOI: 10.1021/jp906978v
|View full text |Cite
|
Sign up to set email alerts
|

Strong Specific Hydroxide Ion Binding at the Pristine Oil/Water and Air/Water Interfaces

Abstract: Despite claims, based largely on molecular dynamics simulations, that the surface of water at the air/water interface is acidic, with a positive charge, there is compelling experimental evidence that it is in fact basic, with a negative charge due to the specific adsorption of hydroxide ions. The oil/water interface behaves similarly. The pH dependence of the zeta potentials of oil drops has been measured by two very different techniques: on a single drop in a rotating electrophoresis cell and on about 10(14) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
248
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(294 citation statements)
references
References 36 publications
42
248
0
4
Order By: Relevance
“…al (1996) investigated emulsions of different non-polar oils (xylene, dodecane, hexadecane and perfluoromethyldecalin) and found practically the same zeta potential under identical experimental conditions for all systems. This result was confirmed by the investigations of Creux et al (2009) who found similar pH dependencies of the zeta potential of nitrobenzene, benzene, octane, decane and dodecane. Thus, the electrostatic effects appear to be nearly independent from the type of oil, and zeta potential measurements of one specific oil can be adopted universally.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…al (1996) investigated emulsions of different non-polar oils (xylene, dodecane, hexadecane and perfluoromethyldecalin) and found practically the same zeta potential under identical experimental conditions for all systems. This result was confirmed by the investigations of Creux et al (2009) who found similar pH dependencies of the zeta potential of nitrobenzene, benzene, octane, decane and dodecane. Thus, the electrostatic effects appear to be nearly independent from the type of oil, and zeta potential measurements of one specific oil can be adopted universally.…”
Section: Introductionsupporting
confidence: 80%
“…As the type of oil has a minor influence on the pH dependency of the zeta potential, the presented model can be adapted to several investigations available in literature (e.g. Creux et al (2009), Gray-Weale and Beattie (2009) and Marinova et al (1996)) for different salts and conditions. If proper data is not available, the zeta potential can be measured and its pH dependency can be described with Stern adsorption isotherm and Grahame equation as presented in this work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The weak effect of OH − on interfacial ion populations is particularly intriguing because the negative potential of the air-water interface has been ascribed to strong OH − adsorption to water-hydrophobe interfaces in general. 51,63,64 Figure 4(a), which displays the ratio χ = P 127 /P 79+81 = I − /Br − as a function of NaY concentrations, reveals that ClO 4 − and NO 3 − have the largest depressing effects on P 127 and P 79+81 , respectively. From the relative affinities of Br − (f ≡ 1.0), NO 3 − (f = 1.4), I − (f = 3.1), and ClO 4 − (f = 19) for the air-water interface (previously measured in a similar setup), 6 we infer that I − and Br function of (NaI + NaBr) concentration, displaying a broad minimum at ∼50 μM, in the absence of added electrolytes ( Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, water provides adsorbed [OH ¹ (H 2 O) n ] ions, which bind to positive PE cations, as expected considering the preferential adsorption of negative water cluster ions on hydrophobic surfaces, as is well established in the literature. 15,16 It should be noted that in all cases solvent evaporation from the polymer surface lowers the surface temperature, facilitating water condensation and thus increasing the adsorption of negative water ion clusters. Lubrication of the sliding surfaces could certainly play a role in suppressing charged domain formation, but this should affect both positive and negative domains, which is different from the experimental results.…”
mentioning
confidence: 99%